MEDICAL IMAGE REGISTRATION: CLASSIFICATION, APPLICATIONS AND ISSUES - Alam, Fakhre; Rahman, Sami Ur; Din, Aziz Ud; Qayum, Fawad (Journal of Postgraduate Medical Institute, 2018)
The objective of this paper is to provide a detailed overview on the classification and applications of medical image registration. Issues in medical image registration are also presented along with their promising solutions and research guidelines. In this review, general concepts, classification, applications and issues in medical image registration is presented and analyzed in a comprehensive manner. The methods used for analysis is unique from already published work because we have performed detailed investigation on the classification, applications and issues in medical image registration. The knowledge on the work that has been developed in the area is presented in a compact and systematic form. This work provides contribution to field of medical image registration by providing a useful platform for both researchers and clinicians in the field.